Identification of the hydrate gel phases present in phosphate-modified calcium aluminate binders. (April 2015) - Chavda, Mehul A.; Bernal, Susan A.; Apperley, David C.; Kinoshita, Hajime; Provis, John L.
Abstract: The conversion of hexagonal calcium aluminate hydrates to cubic phases in hydrated calcium aluminate cements (CAC) can involve undesirable porosity changes and loss of strength. Modification of CAC by phosphate addition avoids conversion, by altering the nature of the reaction products, yielding a stable amorphous gel instead of the usual crystalline hydrate products. Here, details of the environments of aluminium and phosphorus in this gel were elucidated using solid-state NMR and complementary techniques. Aluminium is identified in both octahedral and tetrahedral coordination states, and phosphorus is present in hydrous environments with varying, but mostly low, degrees of crosslinking. A 31 P/ 27 Al rotational echo adiabatic passage double resonance (REAPDOR) experiment showed the existence of aluminium–phosphorus interactions, confirming the formation of a hydrated calcium aluminophosphate gel as a key component of the binding phase. This resolves previous disagreements in the literature regarding the nature of the disordered products forming in this system.